The effectiveness of learning media in improving early childhood numeracy skills - Padilla, Rahmi; Rahmi, Tuti (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2025)
Background : The quality of early childhood education in Indonesia faces significant challenges, particularly in developing basic numeracy skills, which serve as a foundation for cognitive development. This condition highlights the urgency of identifying the most effective teaching methods. Aim : This study aims to compare the effectiveness of two teaching methods commonly used in early childhood education: the singing method and the snakes and ladders game method. Previous studies have shown that each method can improve early childhood numeracy skills. However, no research has directly compared these two approaches within a single experimental research design. Method : This study employed a quasi-experimental design using a pretest-posttest control group format, involving 30 children divided into three groups: singing, snakes and ladders, and control. Data were collected through observation sheets and analyzed using one-way ANOVA and post hoc tests. Result : The results of the study showed that both approaches were effective in improving numeracy skills; however, the singing method produced a significantly greater improvement compared to the snakes and ladders method and conventional learning (p < 0.05). Conclusion : These findings provide a new contribution in the form of empirical evidence comparing two commonly used learning approaches in early childhood education and can serve as a basis for recommendations in the development of curricula and instructional strategies for early childhood mathematics learning.